1983
DOI: 10.1139/b83-243
|View full text |Cite
|
Sign up to set email alerts
|

Additional Hyphomycetes from freshwater swamps and hammocks

Abstract: Collections of submerged, decayed plant material from freshwater swamps in Illinois and hammocks in Florida have yielded two new species, Intercalarispora nigra gen. et sp. nov. and Monodictys cruciseptata sp. nov. New records for North America include Zanclospora novae-zelandicae Hughes & Kendrick and Pseudopetrakia kambakkamensis (Subram.) M. B. Ellis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Notes -The Brazilian specimen has smaller conidia than reported in previous descriptions of Z. novae-zelandiae (Hughes & Kendrick 1965, Matsushima 1975, Schoknecht & Crane 1983, Chang 1990. Zanclospora novae-zelandiae has phialides adpressed and arranged in the fertile region which is located at the middle part of the conidiophore, as in Z. austroamericana and Z. bonfinensis.…”
Section: Zanclospora Indicamentioning
confidence: 73%
See 1 more Smart Citation
“…Notes -The Brazilian specimen has smaller conidia than reported in previous descriptions of Z. novae-zelandiae (Hughes & Kendrick 1965, Matsushima 1975, Schoknecht & Crane 1983, Chang 1990. Zanclospora novae-zelandiae has phialides adpressed and arranged in the fertile region which is located at the middle part of the conidiophore, as in Z. austroamericana and Z. bonfinensis.…”
Section: Zanclospora Indicamentioning
confidence: 73%
“…Known distribution -Brazil (Marques et al 2008), New Zealand (Hughes & Kendrick 1965), Japan (Matsushima 1975), Taiwan (Chang 1990), USA (Schoknecht & Crane 1983, Haja et al 2007.…”
Section: Zanclospora Indicamentioning
confidence: 99%
“…Three collections of Z. novae-zelandiae on decaying wood (ILLS34732, ILLS35030, ILLS43049), reported by Schoknecht and Crane [ 21 ] from the USA, have been revised. Based on the published description, the conidia (15.5–23 × 2.3–3.3 μm) and overall characteristics of conidiophores and phialides matched those of Z. falcata and Z. lateriphiala .…”
Section: Resultsmentioning
confidence: 99%
“…However, the large range of conidial lengths provided an opportunity to expand the species concept further, and the published morphological profiles of Z. novae-zelandiae vary considerably. Several authors [ 8 , 20 , 21 , 22 , 23 ] reported Z. novae-zelandiae from different geographical regions with a variable conidial length and introduced other features. The conidiophore wall lacked ornamentation, and some collections contained uniformly unbranched conidiophores.…”
Section: Introductionmentioning
confidence: 99%
“…1 of Kieffer (1973) . Simmonsiella is similar to Intercalarispora ( Schoknecht & Crane 1983 ) in producing intercalary conidia, but differs from the latter in being phragmoseptate and the conidia of Intercalarispora are dictyoseptate.…”
Section: Taxonomymentioning
confidence: 92%